RETRACTED: Legal regulation of cryptocurrencies in Russia and foreign countries: problems and solutions - Budkin Valeriy; Budkin Oleg (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001